Mathematical methods for physical and analytical chemistry - Goodson, David Z., 1958- (Hoboken, N.J. : Wiley, 2011)
"Mathematical Methods for Physical and Analytical Chemistry presents mathematical and statistical methods to students of chemistry at the intermediate, post-calculus level. The content includes a review of general calculus; a review of numerical techniques often omitted from calculus courses, such as cubic splines and Newton's method; a detailed treatment of statistical methods for experimental data analysis; complex numbers; extrapolation; linear algebra; and differential equations"--
12.2 Randomization12.3 Multiple Comparisons; 12.3.1 ANOVA; 12.3.2 Post-Hoc Tests; 12.4 Optimization; Part III. Differential Equations; 13 Examples of Differential Equations; 13.1 Chemical Reaction Rates; 13.2 Classical Mechanics; 13.2.1 Newtonian Mechanics; 13.2.2 Lagrangian and Hamiltonian Mechanics; 13.2.3 Angular Momentum; 13.3 Differentials in Thermodynamics; 13.4 Transport Equations; 14 Solving Differential Equations, I; 14.1 Basic Concepts; 14.2 The Superposition Principle; 14.3 First-Order ODE's; 14.4 Higher-Order ODE's; 14.5 Partial Differential Equations.
Includes bibliographical references and index.
Print version record.
Keywords: Mathematical physics; Chemometrics; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Chemometrics; Mathematical physics; Electronic books; Electronic books